1996
DOI: 10.1002/(sici)1096-8628(19960712)64:1<234::aid-ajmg42>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for high-risk haplotypes and (CGG)n expansion in fragile X syndrome in the Hellenic population of Greece and Cyprus

Abstract: The expansion of the trinucleotide repeat (CGG)n in successive generations through maternal meiosis is the cause of fragile X syndrome. Analysis of CA repeat polymorphisms flanking the FMR‐1 gene provides evidence of a limited number of “founder” chromosomes and predisposing high‐risk haplotypes related to the mutation. To investigate the origin of mutations in the fragile X syndrome in the Hellenic populations of Greece and Cyprus, we studied the alleles and haplotypes at DXS548 and FRAXAC2 loci of 16 indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
2

Year Published

1998
1998
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 17 publications
2
10
2
Order By: Relevance
“…The distribution of CGG repeats was similar to the general Basque sample from Biscay previously analyzed, and the same mode as in other European populations was observed (Macpherson et al, 1994;Chiurazzi et al, 1996a;Syrrou et al, 1996;Zhong et al, 1996;Arrieta et al, 1999b;Patsalis et al, 1999;Larsen et al, 2000).…”
Section: Arrieta Et Alsupporting
confidence: 84%
“…The distribution of CGG repeats was similar to the general Basque sample from Biscay previously analyzed, and the same mode as in other European populations was observed (Macpherson et al, 1994;Chiurazzi et al, 1996a;Syrrou et al, 1996;Zhong et al, 1996;Arrieta et al, 1999b;Patsalis et al, 1999;Larsen et al, 2000).…”
Section: Arrieta Et Alsupporting
confidence: 84%
“…Our population reveals a high prevalence of the FRAXAC1-3 allele among the fragile X cohort also, a finding similar to that seen among the Finns and the Danes (Zhong et al 1996;Larsen et al 2000). (4) A new allele (designated -5) at the FRAXAC2 locus has been identified in our study sample.However, allele frequency distribution at this locus in our nonfragile X controls showed an overall similarity to Western Caucasian (Australia, Europe, and North America) and African-American populations with FRAXAC2-4+ being the most frequent allele Haataja et al 1994;Macpherson et al 1994;Rousseau et al 1995;Syrrou et al 1996;Crawford et al 2000). The Japanese population, the only other Asian population evaluated for polymorphism at this locus, however revealed a dis-tinct modal allele (FRAXAC2-6+) (Richards et al 1994).…”
Section: Discussionsupporting
confidence: 49%
“…Allele frequency distributions at these polymorphic loci have been investigated among control and fragile X chromosomes from diverse ethnic populations worldwide (Haataja et al 1994;Macpherson et al 1994;Richards et al 1994;Syrrou et al 1996;Bonaventure et al 1998;Zhong et al 1999;Crawford et al 2000). However, the majority of these studies have been limited to the Western (White) Caucasian ethnic groups derived primarily from North America, Europe and Australia.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the genetic isolation level appears as an important factor influencing the strength of association. Thus, in the isolated Finnish population 75% of all fragile X chromosomes were linked to a single rare haplotype [Oudet et al, 1993b;Haataja et al, 1994;Zhong et al, 1996], whereas the Greek population showed no particular haplotypes in disequilibrium, possibly as a result of its heterogeneous genetic history [Syrrou et al, 1996].…”
Section: Introductionmentioning
confidence: 96%